Climbing the Stairs to Leadership: Reflections on Moving Beyond the Stained‐Glass Ceiling. Issue 4 (April 2017) - Barnes, Joanne
Abstract : The phrase Times are a changin ' was one that brought hope for a young African American woman who realized the importance of education and hard work. Entering the workforce in the mid‐1970s provided many challenges and the proverbial glass ceiling was even more difficult to conquer for women of color. The move from cashier in the retail industry to a global leader in the automotive industry to administrative leader in higher education provided many the opportunity to learn what it means to be a women leader in an ever‐changing world. The current paper provides an overview of women of color in leadership, leadership behaviors, lessons learned from the field, and what millennial women leaders can do to move from the status quo to leadership excellence.